Influence of Attitudes on the Autonomy of English as a Foreign Language Teachers - Lina Qian; Xuewu Qin; Ziyu Wei; Haiquan Huang (Education Sciences)
In applied linguistics, teacher professional development and teacher autonomy have long been hot research topics. However, little attention has been paid to the issue of what attitudes teachers hold toward their professional development. Furthermore, it remains unknown whether teacher autonomy is influenced by the aforementioned attitudes. Under this circumstance, the current study attempts to explore what attitudes English as a Foreign Language (EFL) teachers hold toward their professional development and whether such attitudes influence teacher autonomy. For this purpose, we investigated 14 EFL teachers, using classroom observation, stimulated recall interview and semi-structured interview, respectively. The collected data were analyzed in light of the grounded theory, which gave rise to three main findings. First, the participants’ autonomy was positively correlated with their attitudes toward professional development. Second, most of the participants held a negative attitude toward their professional development. Third, the participants held conflicting opinions about the influence of in-service training on professional development. These findings indicate that EFL teachers’ professional identity is positively correlated with teacher autonomy. Moreover, the findings call for effective measures to improve EFL teachers’ attitudes toward their professional identity.